Efficacy of acceptance and commitment therapy in daily life in early psychosis: results from the multi-center INTERACT randomized controlled trial - Myin-Germeys, Inez; van Aubel, Evelyne; Vaessen, Thomas; Steinhart, Henrietta; Klippel, Annelie; Lafit, Ginette; Viechtbauer, Wolfgang; Batink, Tim; van Winkel, Ruud; van der Gaag, Mark; van Amelsvoort, Therese; Marcelis, Machteld; et al. (Psychotherapy and psychosomatics, 2022)
Introduction/Objective: This study aimed to investigate efficacy of Acceptance and Commitment Therapy in Daily Life (ACT-DL), combining face-to-face therapy with an Ecological Momentary Intervention (EMI), in addition to treatment as usual (TAU) for psychotic distress, in comparison to TAU. Methods: Individuals aged 15-65 years with clinically established ultra-high risk or first episode of psychosis were randomly assigned to TAU or ACT-DL+TAU. ACT-DL+TAU consisted of 8 ACT-sessions augmented with an EMI-app. The primary outcome was psychotic distress assessed with the Comprehensive Assessment scale of At Risk Mental State (CAARMS) at post-intervention and 6- and 12-month follow-up. Secondary outcomes were functioning, symptom severity, and momentary psychotic distress. We performed multivariate mixed models according to intent-to-treat principles. Results: Between June 1, 2015 and December 31, 2018, 668 participants were referred, of whom 148 were randomized to ACT-DL+TAU (n = 71) or TAU (n = 77). One hundred and fifteen (78%) provided primary outcome data at least at one follow-up assessment. There was no evidence of greater reduction in the primary outcome measure CAARMS distress in ACT-DL+TAU compared to TAU (χ2(3) = 2.36; p = 0.50). However, out of the tested secondary outcomes, global functioning (χ2(3) = 9.05; p = 0.033), and negative symptoms (χ2(3) = 19.91; p<0.001) improved in ACT-DL+TAU compared to TAU, as did momentary psychotic distress (χ2(3) = 21.56; p < 0.001). Conclusions: INTERACT did not support a significant effect of ACT-DL over TAU on the primary outcome measure of psychotic distress as assessed with the CAARMS. Although significant improvements were found for some secondary outcome measures, further replication studies are needed to confirm the strength and specificity of these effects.